MOLECULAR DOCKING ANALYSIS OF SELECTED CURCUMA XANTHORRHIZA CONSTITUENTS AS POTENTIAL ANTICANCER DRUG - Akhmad Endang Zainal Hasan; I Made Artika; Suryani; Dhani Luthfi Ramadhani (BIOTROPIA, 2023)
Stress conditions will trigger the histone hyperacetylation process due to histone acetyltransferase p300/CBP (HAT PCAF) constantly transfers acetyl groups from acetyl-CoA to conserved lysine residues on histone proteins to form ε-N-acetyllysine. This can be a cause of cancer. The purpose of this study was to investigate the potential mechanisms and inhibition of PCAF HAT by chemical components of C. xanthorrhiza namely, curcumin, demethoxycurcumin, bisdemethoxycurcumin, and xanthorrizhol using in silico, the molecular docking method.  Results showed that the components of C. xanthorrhiza as ligands have the capability to inhibit the binding of acetyl-CoA to histone. These results can be used to predict the inhibitory mechanisms exhibited by C. xanthorrhiza components, as competitive and noncompetitive substances. We hypothesize that C. xanthorrhiza components resemble a substrate, leading to prevention of the natural substrate (histone) to bind to the enzyme, and hence block the product formation. The smallest free Gibs energy was exhibited by curcumin on chain B and by bismethoxycurcumin on chain A, with values of -8.8 and -8.4 Kcal/mol, respectively.